DEVELOPING READING SKILL OF ISLAMIC EDUCATION DEPARTMENT STUDENTS THROUGH GUIDED READING - Marzuki, Abdul Gafur (Paedagogia: Jurnal Pendidikan, 2016)
This classroom action research was conducted to Develop reading skill by implementing guided reading of the second semester students of Islamic Education Department FTIK IAIN Palu. This research employed action research design consisted of one cycle and seven meetings. Six meetings were held to conduct the teaching-learning process by implementing the Guided reading technique, and one meeting was held to evaluate the students’ individual achievement. The researche’s role is to help the students’ to find out the determining the main idea, find the specific information, locate the reference (people and thing) and find out implicit information in the text. Based on the result of observation sheet on students activities it was 28 (93.34%) out of 30 students who got scores over 70, students could get the score above the standard score namely70. It means that the main criterion; the students’ achievement in this research already meets. It indicated that the implementation of the Guided Reading in teaching reading skill to the students was effective.